Behind the Screen of Hajj News on Television: Strategies and Challenges - Prastya, Narayana Mahendra; Setiadi, Anggi Arif Fudin; Ningsih, Ida Nuraini Dewi Kodrat (Universitas Islam Indonesia, 2025)
This article aims to analysis on how Indonesian television media make news coverage about hajj. Indonesia is a second largest Muslim popoulation country, it make the news about Islam will attract Muslim community attention, including hajj. Although television viewer tend to decline, but Indonesian still interested in television. Additionaly, the television news production have more complexities comparing with printed, radio, and online media. Research use qualitative methods with data sources interview with television journalist from four different television station, who depart to Saudi Arabia in order make news coverage in Hajj year 2022. Results shows Indonesian media focus to educate audience on health issue, because 2022 was the first time hajj re-open after the Covid-19 pandemic. Antoher theme were update about Indonesian pilgrims situation, feature news and soft news about unique things in Saudi Arabia. Indonesian journalist applied solo journalism practice and use only smartphone for information gathering and processing. Indonesian journalist joined in Media Center Haji (MCH) formed by Ministry of Religious Affair Republic Indonesia. In the MCH, journalist collaborate each other by sharing the raw information on the storage. Challenges in news reporting was the restriction rules impose by Saudi Arabia government, especially in taking or recording picture.